2019
DOI: 10.1097/jhq.0000000000000227
|View full text |Cite
|
Sign up to set email alerts
|

Physician Practices in Against Medical Advice Discharges

Abstract: Background: Patients discharged against medical advice (AMA) have disproportionately high health care costs and increased morbidity, mortality, and hospital readmissions. Although patient risk factors for discharge AMA are known, there are little data regarding physician discharge practices surrounding AMA discharges. Methods: We performed a cross-sectional analysis of patients discharged AMA from a large, urban, academic medical center. Our study predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Interestingly, this study did not show a relationship between physician discharge practices and risk of readmission. 31…”
Section: Risk Factorsmentioning
confidence: 99%
“…Interestingly, this study did not show a relationship between physician discharge practices and risk of readmission. 31…”
Section: Risk Factorsmentioning
confidence: 99%
“…In one study, among all patients who left AMA, only 33% had follow-up appointments, 63% had informed consent, and 69% of patients had documentation of risk and benefits and discussion with the physician. However, these practices were not shown to be associated with increased 30-day readmission 10,13,14 . Patients leaving AMA result in a higher cost to the health care system after readmission.…”
Section: Discussionmentioning
confidence: 89%
“…In addition, we did not have details of the patient's insurance status, cost of care, and post-AMA physician follow-up status, which can independently affect a patient's long-term outcome. [13][14][15][16] Our study participants did not have uniform access to a specialist in substance use disorder or a psychiatrist. Multidisciplinary treatment of these patients with specialists in substance use disorders and psychiatry might contribute to improving the management of these patients in terms of reducing AMA rates and further hospitalizations.…”
Section: Risk Factorsmentioning
confidence: 99%
“…They should go through the discharge process like any other discharge: give instructions, inform patients of any investigations that may have been conducted before discharge and provide the relevant prescriptions [ 30 , 32 , 37 ]. Even though it has been shown that up to 94% of attending physicians agree that AMA patients should receive medication and follow-up arrangements [ 40 ], studies indicate that only a quarter of these patients do receive a prescription and that only a third of them are discharged with a follow-up plan [ 40 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…Exhaustive documentation was found in only 4% of the charts in a small study [44]. Capacity is documented in about 20-60% of files [30,[40][41][42]44], and a discussion about risks is documented in about 60-70% of files [30,42]. The primary reason to designate the discharge as AMA is the fear of legal liability [33].…”
Section: Documentationmentioning
confidence: 99%